2020
DOI: 10.1167/jov.20.8.8
|View full text |Cite
|
Sign up to set email alerts
|

Brief period of monocular deprivation drives changes in audiovisual temporal perception

Abstract: The human brain retains a striking degree of plasticity into adulthood. Recent studies have demonstrated that a short period of altered visual experience (via monocular deprivation) can change the dynamics of binocular rivalry in favor of the deprived eye, a compensatory action thought to be mediated by an upregulation of cortical gain control mechanisms. Here, we sought to better understand the impact of monocular deprivation on multisensory abilities, specifically examining audiovisual temporal perception. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…Noticeably, the visual MD effect emerged here for the Deprived eye, while the audio-visual MD effect emerged only for the Undeprived eye. While these effects are in line with previous behavioral studies (Lo Verde et al, 2017; Opoku-Baah and Wallace, 2020), they also support a crucial role of MD in inducing flexible alterations of interocular excitability balance and, in turn, in audio-visual processes. Moreover, although an interaction between MD and eye dominance cannot be excluded, a recent study reported that the MD effect was the same regardless of whether the dominant or the non-dominant eye was deprived (Schwenk et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Noticeably, the visual MD effect emerged here for the Deprived eye, while the audio-visual MD effect emerged only for the Undeprived eye. While these effects are in line with previous behavioral studies (Lo Verde et al, 2017; Opoku-Baah and Wallace, 2020), they also support a crucial role of MD in inducing flexible alterations of interocular excitability balance and, in turn, in audio-visual processes. Moreover, although an interaction between MD and eye dominance cannot be excluded, a recent study reported that the MD effect was the same regardless of whether the dominant or the non-dominant eye was deprived (Schwenk et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Previous behavioral studies have shown that multisensory perception can be altered by MD (Lo Verde et al, 2017;Opoku-Baah and Wallace, 2020). By measuring changes in neural oscillations, we assessed neural mechanisms underpinning multisensory short-term plasticity and revealed the specific enhancement of induced gamma activity [65][66][67][68][69][70][71][72][73][74][75] selectively for the Undeprived eye when processing audio-visual input.…”
Section: The Impact Of MD On Audio-visual Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the lack of PSS shift under binocular viewing is consistent with studies that have assessed the impact on audiovisual temporal perception by visual phenomena that modulate perceived stimulus effectiveness. For example, Opoku-Baah and Wallace 63 showed that a brief period of monocular deprivation, a phenomenon known to boost perceived contrast in the deprived eye, did not significantly affect the PSS, although changes in the TBW were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect of multisensory interactions that are affected by monocular deprivation includes the temporal binding of two multisensory stimuli. The deprived eye presents a sharper temporal acuity, whereas the non-deprived eye shows poorer temporal acuity after 1.5 hours of monocular deprivation (Opoku-Baah and Wallace 2020). These results are in line with homeostatic plasticity describing that the brain compensates the deprivation effect by enhancing the signals from the deprived eye.…”
Section: Visual Deprivation In the Sightedmentioning
confidence: 99%